Strategic Public Relations in Building and Developing Corporate Image After Reputational Crisis - Diana Candraningrum; Nawang Ayu Romadoni; Nenny Anggraini; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
Corporate governance crises have increasingly become a critical challenge for organizations as they can significantly damage reputation and weaken stakeholder trust. When governance failures such as ethical violations, corruption, or weak internal oversight occur, organizations may face substantial reputational pressure that threatens their legitimacy in the eyes of the public. In this context, effective crisis communication and strong governance mechanisms are essential to restore public confidence and maintain long-term organizational credibility. This article aims to develop a conceptual model explaining the process of corporate image development following a governance-related reputational crisis. Using a qualitative descriptive approach and literature-based conceptual analysis, the study integrates perspectives from crisis communication theory, stakeholder theory, and corporate governance literature to examine the relationships among crisis responsibility attribution, crisis response strategies, transparency, stakeholder engagement, and trust restoration. The analysis suggests that governance crises influence public attribution of organizational responsibility, which subsequently shapes the selection of crisis communication strategies. Transparent communication and corrective actions play a central role in reducing uncertainty and demonstrating accountability during the crisis recovery process. Furthermore, stakeholder engagement is identified as a critical mechanism that facilitates trust restoration and strengthens long-term corporate image development. The proposed conceptual model contributes to the literature by integrating multiple theoretical perspectives to provide a more comprehensive understanding of reputational recovery and sustainable image development in contemporary organizations.